Learning path : C++ game programming. - Horton, John; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"Looking to learn C++ from scratch and simultaneously build stunning and interactive games? Explore this Learning Path and you will get more than expected. Start as an amateur and rise as a pro by taking this Learning Path. This Learning Path is a fun journey to the world of game programming starting from the basics of C++ such as OOP, pointers, introduction to the Standard Template Library, and finally building OpenGL-powered SFML fully-playable complex games. These games are an addictive frantic two-button tapper, a multi-level zombie survival shooter, and a split-screen multiplayer puzzle-platformer. You will explore exciting game programming concepts such as particle effects, directional sound, OpenGL programmable Shaders, spawning thousands of objects, and more."--Resource description page.
Beginning C++ game programming, Part 1 / John Horton -- Beginning C++ game programming, Part 2 / John Horton.
Title and publication information from resource description page (Safari, viewed March 3, 2017).
Keywords: C++ (Computer program language); Computer games -- Programming; Computer games -- Design; Electronic books